2018
DOI: 10.1002/ijc.31939
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation reflects spatial heterogeneity and molecular evolution of lung adenocarcinomas

Abstract: Lung adenocarcinoma (ADC) is the most prevalent subtype of lung cancer and characterized by considerable morphological and mutational heterogeneity. However, little is known about the epigenomic intratumor variability between spatially separated histological growth patterns of ADC. In order to reconstruct the clonal evolution of histomorphological patterns, we performed global DNA methylation profiling of 27 primary tumor regions, seven matched normal tissues and six lymph node metastases from seven ADC cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…In addition, three independent validation datasets including GSE114989, GSE83842, and GSE85845 were obtained from the GEO [20]. GSE114989 [21] included 27 primary tumors and 7 matched normal tissues from 7 LUAD patients, GSE83842 [22] contained 12 cases with paired tumor and normal tissue, and GSE85845 [23] included 8 LUAD and adjacent nontumor tissues.…”
Section: Dna Methylationmentioning
confidence: 99%
“…In addition, three independent validation datasets including GSE114989, GSE83842, and GSE85845 were obtained from the GEO [20]. GSE114989 [21] included 27 primary tumors and 7 matched normal tissues from 7 LUAD patients, GSE83842 [22] contained 12 cases with paired tumor and normal tissue, and GSE85845 [23] included 8 LUAD and adjacent nontumor tissues.…”
Section: Dna Methylationmentioning
confidence: 99%
“…ITH is a well-described phenomenon in lung adenocarcinoma (ADC) on a radiologic, histopathologic, genetic, epigenetic, and tumormicroenvironmental level. [22][23][24][25][26][27][28][29][30][31] According to the most widely accepted theory, ITH is mainly the result of subclonal evolution during natural tumor progression and therapeutic interventions. 32,33 The great molecular variability associated with high levels of ITH is seen as one of the leading causes for lack of response or development of resistance under therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that areas with high DNA methylation (such as CpG islands) are accompanied by copy number variation, and these genomic variations affect the level of DNA methylation [23]. For example, in lung adenocarcinoma, DNA methylation heterogeneity 4 demonstrates branch clonal evolution of lung adenocarcinoma regions driven by genomic instability, and subclone copy number variation [24]. Here, we investigated the association between genomic variation (such as CNV) in regulatory regions of BRCA and corresponding changes in DNA methylation.…”
Section: Introductionmentioning
confidence: 99%